2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2550.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin status during normal pregnancy and postpartum: a longitudinal study comprising 406 Danish women

Abstract: Low cobalamin status may occur among pregnant women, especially in late pregnancy. The recommendations for periconceptional vitamin B(12) supplementation should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 13 publications
10
66
4
4
Order By: Relevance
“…Ten of the 11 studies that reported the mean showed a consistent decrease in vitamin B-12 concentrations from the first to the third (91,95), from the second to the third (28,45,46,81,87), and from the first to the second to the third (85,96,98) trimesters. The exception was the study by Marzan et al (83), which showed a marginal increase in mean vitamin B-12 concentrations across the pregnancy (266, 270, and 286 pmol/L in the first, second, and third trimesters, respectively), despite the participants not (19,84).…”
Section: Mean Vitamin B-12 Concentrations Across Trimestersmentioning
confidence: 92%
“…Ten of the 11 studies that reported the mean showed a consistent decrease in vitamin B-12 concentrations from the first to the third (91,95), from the second to the third (28,45,46,81,87), and from the first to the second to the third (85,96,98) trimesters. The exception was the study by Marzan et al (83), which showed a marginal increase in mean vitamin B-12 concentrations across the pregnancy (266, 270, and 286 pmol/L in the first, second, and third trimesters, respectively), despite the participants not (19,84).…”
Section: Mean Vitamin B-12 Concentrations Across Trimestersmentioning
confidence: 92%
“…Vitamin B12 can only be obtained from animal products [63]. More than 1000 μg of vitamin B12 is stored in fertile women eating a mixed diet 63 . At term, foetal vitamin B12 stores should be 25-50 μg 64 .…”
Section: Vitamin B-12 Deficiencymentioning
confidence: 99%
“…Plasma cobalamins 2 were measured on the Microparticle Enzyme Immunoassay technology (Abbott Diagnostics, IL, USA). ELISA assays were used to measure TC and HC (holo and total) in serum.…”
mentioning
confidence: 99%